PSVII-22 Trichostatin A as an aging agent in an oocyte. (30th November 2020) - Arena, Haley A; Hicks, Emma C; Whitaker, Brian
Abstract: As oocytes experience prolonged aging, reactive oxygen species (ROS) typically accumulate, the mitochondrial electrochemical potential gradient dissipates, and cumulus cells undergo expansion. Trichostatin A (TSA), used to stimulate aging, delays oocyte maturation by inhibiting germinal vesicle breakdown during meiosis. The objective of this study was to study the effects of aging during in vitro oocyte maturation in pigs. Oocytes (n=881) were matured with or without TSA (100 ng/mL) for 24 or 48 h followed by an additional 16 h of maturation without TSA. At the end of maturation, oocytes (n=446) were evaluated for cumulus cell expansion (CCE). A portion of the oocytes were stained to determine the relative levels of ROS (n=476) or mitochondrial electrochemical potential gradient dissipation (n=405). Fluorescent images of the oocytes were acquired, images were analyzed using ImageJ, and statistical analysis of the data was performed using ANOVA and Tukey's test. Oocytes matured with or without TSA for 48 h had significantly less (P < 0.05) CCE compared to oocytes matured without TSA for 24 h. Oocytes matured without TSA for 24 h generated significantly different (P < 0.05) levels of ROS compared to oocytes matured with TSA for 48 h. Oocytes matured without TSA for 48 h had significantly higher (P < 0.05) mitochondrial membrane potential compared to the all other treatments. Results indicate that oocytes experiencing prolonged aging have less CCE and a decrease in mitochondrial membrane potential but no consistent or predictable trends in ROS formation. The use of TSA to stimulate aging in pig oocytes remains a valid and a reliable option.